MECHANICAL STRESS-STRAIN ANALYSIS OF A PORTABLE OIL SPILL SKIMMER FRAME FOR RESPONSE AND RECOVERY ACTIVITIES - Ramanathan, R.; Abdullah, L.; Md Fauadi, M.H.F.; Syed Mohamed, M.S.; Aras, M.S.M; Nur Chairat, A.S. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Oil spillage has been a problem for over a decade, and proper measures must be taken to address it. Boom barriers and skimmer absorbent materials can be used to contain oil spills. However, problem occurs during high tides and strong waves, where the boom and skimmer reconstruction is necessary as the oil could pass over the barrier. Therefore, a portable oil spill skimmer prototype complemented the existing technique. However, it lacked robustness in the frame structure while coping with rough seas. To improve the portable oil spill skimmer's mechanical performance, this article addresses the enhancement of the Portable Oil Spill Skimmer's frame. Thus, this study objective is to analyze the structural analysis of the improved portable oil spill skimmer frame. The structure was analyzed in terms of deformation, equivalent stress, and strain analysis to identify the structural behavior and failure before fabricating the product. The significance of the study is to analyze the frame structure and determine if the frame can be fabricated and used without failure. The FEA results show that the maximum equivalent stress, maximum equivalent strain, and total deformation values are 16.851 MPa, 0.25896e-3 mm/mm, and 0.3742 mm, respectively. Moreover, the enhanced frame could withstand 39kg of weight, and the safety factor is 3.019. In conclusion, the portable oil spill skimmer frame could survive rough seas and withstand 39kg of weight.